Beneath cold seas : exploring cold-temperate waters of North America - Rotman, Jeffrey L.; Allen, Barry (Barry W.) (New York : Van Nostrand Reinhold, 1983)
Describes the cold water marine life of New England, California, Washington and British Columbia. Includes numerous colour photographs.
Keywords: Marine biology -- Atlantic Coast (United States); Marine biology -- British Columbia -- Pacific Coast; Marine biology -- Pacific Coast (United States).